SUCCESSES AND CHALLENGES IN LESSON STUDY OF SCIENCE TEACHERS IN FUKUYAMA CITY, JAPAN - Dave, Angeles; Takuya, Matsuura (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This paper examines the advantages and disadvantages of Lesson Study among junior high school science teachers in Fukuyama City, Hiroshima, Japan. Using the descriptive-survey research design to the two groups (young teachers and veteran teachers) of all the junior high school science teachers in Fukuyama City, assessment on the successes and challenges on Lesson Study was carried out. Survey questionnaire, interview, and observation sheets were used to assess the three categories namely professional development, administrative support, and team cooperation among the teachers, in the implementation of Lesson Study. The deep views and opinions were probed using open-ended questions. It was found out that science teachers achieved successes in terms of professional development, administrative support, and team cooperation. However, the challenge faced by teachers is the availability of time. The t-test of independent means made on the relevant data of the two groups implies that young and veteran teachers are of equal variances in terms of their successes and challenges in Lesson Study.